2010
DOI: 10.1098/rspb.2010.0171
|View full text |Cite
|
Sign up to set email alerts
|

The shrinking ark: patterns of large mammal extinctions in India

Abstract: Mammal extinctions are widespread globally, with South Asian species being most threatened. We examine local extinctions of 25 mammals in India. We use historical records to obtain a set of locations at which each species was known to have been present at some time in the last 200 years. We then use occupancy estimation models to draw inferences about current presence at these same locations based on field observations of local experts. We examine predictions about the influence of key factors such as protecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
124
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 161 publications
(129 citation statements)
references
References 31 publications
5
124
0
Order By: Relevance
“…For example, Lagendijk & Gusset [66] found that some people living around the greater Kruger area in South Africa do not kill lions even when they suffer economic losses and no compensation is available, and suggest that this is because of 'cultural tolerance'. In fact evidence suggests that cultural tolerance of species, including carnivores, reduces extinction probabilities [67]. Compensation for livestock killed by carnivores may be important to encourage commercial farmers to tolerate carnivores [30].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Lagendijk & Gusset [66] found that some people living around the greater Kruger area in South Africa do not kill lions even when they suffer economic losses and no compensation is available, and suggest that this is because of 'cultural tolerance'. In fact evidence suggests that cultural tolerance of species, including carnivores, reduces extinction probabilities [67]. Compensation for livestock killed by carnivores may be important to encourage commercial farmers to tolerate carnivores [30].…”
Section: Discussionmentioning
confidence: 99%
“…False positive detections induced significant bias, and as misidentifications increased, bias also increased. Data collection methods where false positive errors are known to occur such as large-scale volunteer-based surveys (e.g., Weir and Mossman 2005), interviews with local experts (Karanth et al 2010, Zeller et al 2011), use of historical records (Boessenkool et al 2010), call surveys (Simons et al 2007, McClintock et al 2010a, computer algorithms to FIG. 3.…”
Section: Discussionmentioning
confidence: 99%
“…With large mammals increasingly confined to protected areas (Ceballos et al 2005;Karanth et al 2010), understanding how to maintain landscape-scale ecological processes that support diverse mammal communities within reserve boundaries is a critical conservation priority (Woodroffe & Ginsberg 1998;Bengtsson et al 2003;Berger 2004;van Aarde & Jackson 2007;Loarie et al 2009a, b). Sustainable predatoreprey interactions exemplify con-ditions that are difficult to achieve within protected areas (Sinclair et al , 2008Tambling & Du Toit 2005;Ripple & Beschta 2006;Hayward & Somers 2009).…”
mentioning
confidence: 99%